Comparison of ground motions estimated from prediction equations and from observed damage during the M = 4.6 1983 Liège earthquake (Belgium) - D. García Moreno (Natural Hazards and Earth System Sciences, 2013)
On 8 November 1983 an earthquake of magnitude 4.6 damaged more than 16 000 buildings in the region of Liège (Belgium). The extraordinary damage produced by this earthquake, considering its moderate magnitude, is extremely well documented, giving the opportunity to compare the consequences of a recent moderate earthquake in a typical old city of Western Europe with scenarios obtained by combining strong ground motions and vulnerability modelling. The present study compares 0.3 s spectral accelerations estimated from ground motion prediction equations typically used in Western Europe with those obtained locally by applying the statistical distribution of damaged masonry buildings to two fragility curves, one derived from the HAZUS programme of FEMA (FEMA, 1999) and another developed for high-vulnerability buildings by Lang and Bachmann (2004), and to a method proposed by Faccioli et al. (1999) relating the seismic vulnerability of buildings to the damage and ground motions. The results of this comparison reveal good agreement between maxima spectral accelerations calculated from these vulnerability and fragility curves and those predicted from attenuation law equations, suggesting peak ground accelerations for the epicentral area of the 1983 earthquake of 0.13–0.20 g (g: gravitational acceleration).